Vernicia calcicola (Euphorbiaceae), a new species from limestone areas of Guangxi, China - Nong, Dong-Xin; Hu, Ren-Chuan; Huang, Yun-Feng; Yu, Li-Ying (Phytotaxa, 2023)
Vernicia calcicola (Euphorbiaceae) discovered in limestone areas along the Sino-Vietnam boundary (Guangxi Province, China) is described, illustrated and compared with its allied species. A detailed description, illustration, photographs, distribution, ecology, phenology and relevant notes are provided.